Outcome of remedial coaching in Biochemistry with peer assisted learning as teaching learning methodology – An observational study among undergraduate medical students - Arvindrao Dambal, Amrut; V, Nimisha; K Padaki , Samata; Kumar, Saurabh; Rangrez, Shadab; Rathod D, Vinod; Tangadi , Deepak (Journal of Neonatal Surgery, 2025)
Introduction: Peer-assisted remedial teaching (PART) is an inclusive educational approach that fosters a collaborative learning environment. It encourages students with varying proficiency levels to engage in reciprocal teaching relationships, where more capable students provide guidance and support to their peers. This strategy is designed to enhance learning outcomes, boost confidence and improve academic performance through targeted intervention. This study aimed to assess the effectiveness of peer-assisted teaching for slow learners among medical students, evaluating its impact on academic performance, student engagement, and overall learning experience. Material and methods: Peer-assisted structured remedial tutoring was provided by peer tutors to slow learners at regular intervals during the second and third block of learning in biochemistry during 1st MBBS. The 1st Internal Assessment (IA) scoring pattern was compared with the 2nd IA, Prefinal assessment and Final summative examination. Results: The average scoring pattern (%) was 34.29 ± 5.98 in 1st IA and showed a significant improvement to 46.33 ± 11.97, 51.08 ± 9.65 and 52.34 ± 11.47 in 2nd IA, pre-final and final examination. Repeated Measures ANOVA proved that there was a significant effect of PART in increasing the academic performance of slow learners (Wilks’ Lambda = 0.194, F (3, 24) = 33.24, p < 0.005, η2 = 0.80). There was significant improvement in the academic performance in short term and long-term analysis. Peer mentors improved their knowledge-retaining abilities, reinforcing their learning while helping others. Conclusion: PART has shown promising potential as a valuable tool for enhancing slow learners’ academic performance and confidence in medical education.